From self-reflection to self-regulated learning: Do metacognitive prompts with digital tool support? - PriyantinTina; SuherdiDidi; YusufFazri Nur (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
As we enter the era of digital learning, technological advancements have accelerated the demand for self-regulated learning (SRL) and opened up new learning options that may encourage the development of self-control skills. This study aims to provide metacognitive prompts in self-reflection activity by using a digital tool as well as to investigate how students build their metacognitive strategies to regulate their learning. This qualitative study was conducted to 32 EFL pre-service teachers joining the Micro Teaching course. They were assigned to write a self-reflection after they did their teaching practices through a digital tool called Grokspot which is used for feedback, reflection and discussion. Four question prompts for each reflection were inserted into the task instructions and each reflection posting was analyzed by using SRL microanalysis to find out the metacognitive strategies that support self-regulation. The findings revealed that the digital tool facilitated the participants to explore reflection more easily and motivate them to participate in the activities. In the first self-reflection, most students organized their reflections based on the prompts by monitoring and evaluating their performances although many of them still depended on the instructor and peer feedback. Furthermore, specific metacognitive strategies still couldn’t be identified much from most reflections regarding future planning or strategies to improve their performances, However, since scaffolding was given more intensively on the second self-reflection activity, their awareness of metacognitive strategies was found more significant in terms of two dimensions of self-regulated learning; metacognition and environment regulation. Implications of the study are discussed based on the findings.